The Role of Artificial Intelligence in Knowledge Management Implementation: An Inductive Study - Al-Fazari, Arif Khamis; Echaoui, Abdellah (Journal of Economic, Administrative and Legal Sciences, 2024)
This research paper aimed to explore the role of artificial intelligence (AI) in implementing knowledge management within organizations, as knowledge management significantly contributes to enhancing organizational performance, fostering innovation, and enabling adaptability. With the advancement of AI technologies, these sophisticated tools can improve the processes of information gathering, analysis, and dissemination more effectively. The study discusses how AI facilitates knowledge transfer, enhances decision-making, and strengthens organizational communication. The study relied on extrapolating and analyzing previous research to assess the impact of AI on knowledge management. Reports, such as the Gartner 2023 report, indicated that AI applications could improve cognitive process efficiency by up to 40%. Similarly, a 2022 study by McKinsey demonstrated that organizations that utilize AI-supported knowledge management saw a 20% increase in productivity. The study further reviewed the advantages of integrating AI into knowledge management, such as promoting innovation, with AI-implementing companies achieving a 25% increase in innovation, according to Harvard Business Review 2020. Furthermore, PwC’s 2022 findings revealed that 72% of companies using AI achieved better decision-making outcomes. Conversely, despite these benefits, organizations face challenges in integrating AI, including resistance to change and infrastructural limitations. Accenture’s 2023 study emphasized that AI contributes to achieving strategic organizational goals by enhancing knowledge processes and supporting data-informed decisions in innovative work environments.